ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN LABA - sri wahyuti; Syarifah Lulu Damanti; Roger Antolin (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2023)
This study aims to be able to analyze and measure the factors that influence profit growth. The sample in this study were 14 transportation sub-sector companies listed on the IDX for the 2017-2021 period which matched the sample criteria. The type of research used in this research is descriptive quantitative. The type of data used in this research is secondary data. Secondary data derived from publications in the Indonesia Stock Exchange (IDX). Data collection using documentation techniques. The type of data in this study is secondary data derived from publications on the Indonesia Stock Exchange by collecting data using documentation techniques.The data analysis method uses descriptive statistical analysis which describes a data that can be seen from its value. Using the classic assumption test which is a statistical requirement that must be met in multiple linear analysis based on ordinary least squares. The results of the study show that Current Ratio, Total Asset Turnover, and Net Profit Margin are factors that influence profit growth in transportation sub-sector companies listed on the IDX for the period 2017 – 2021.